MORAL VALUE AND CHARACTER BUILDING EDUCATION IN BATAK TOBA’S BATU GANTUNG - Mentary indrayana tampubolon; Rointan friska simbolon; Dessy natalia br Sitepu; Febrianti atalia purba (English Language Teaching Prima Journal (ELT), 2020)
Abstract This research was Conducted by using Library Research Method. Based on the problem of the study above, the objective of the study are to find out the moral values found in the Batak Toba’s Batu gantung folklore and to find out the moral values found in Batak Toba’s Batu Gantung applied in Students’ character building. In this research, the writer used qualitative method because this study focuses on the evaluation or interpretation of the written fabric in context. Materials can encompass textbooks, newspapers, magazines, papers, films, manuscripts, articles, and many others. To achieve easiness of this study and to reply the research problem, after the data have been collected, then the creator analyzed them systematically. After analyzing the folklore, the researcher found some moral lessons and character building education such as; kindness,compassion, courage, enthusiasm, justice, responsibility, and caring. Keywords: moral value, batu gantung folklore, character building